2016
DOI: 10.1007/s12471-016-0902-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic activity in chronic heart failure: cardiac 123I-mIBG scintigraphy to improve patient selection for ICD implantation

Abstract: Heart failure is a life-threatening disease with a growing incidence in the Netherlands. This growing incidence is related to increased life expectancy, improvement of survival after myocardial infarction and better treatment options for heart failure. As a consequence, the costs related to heart failure care will increase. Despite huge improvements in treatment, the prognosis remains unfavourable with high one-year mortality rates. The introduction of implantable devices such as implantable cardioverter defib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Heart failure is a life-threatening disease with a growing incidence in developed countries due to better treatment options for heart failure, improvement of survival after myocardial infarction, and increased life expectancy. The introduction of implantable devices such as implantable cardioverter defibrillators (ICD) has improved the overall survival of patients with heart failure [ 20 ]. ICD treatment reduces mortality in patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure is a life-threatening disease with a growing incidence in developed countries due to better treatment options for heart failure, improvement of survival after myocardial infarction, and increased life expectancy. The introduction of implantable devices such as implantable cardioverter defibrillators (ICD) has improved the overall survival of patients with heart failure [ 20 ]. ICD treatment reduces mortality in patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…The myocardium scintigraphy with 123I-MIBG in recent years have become very widespread, due to the proved fact of its diagnostic value in predicting cardiac death, progression of heart failure, the occurrence of life-threatening arrhythmias in patients with heart failure [11]. It is believed that the nervous tissue of the heart is more sensitive to ischemia than the muscular tissue, so the defects of accumulation of 123I-MIBG in patients with CAD are larger in size compared with the defects of accumulation of perfusion radiopharmaceuticals [12].…”
Section: рис 2 сцинтиграфия миокарда с 99mтс-мибгmentioning
confidence: 99%
“…In a number of studies, the higher significance of SPECT with 123I-MIBG was shown in comparison with myocardial perfusion scintigraphy in the prognosis of motivated shocks of ICD, implanted for primary prevention of sudden cardiac death [11].…”
Section: рис 2 сцинтиграфия миокарда с 99mтс-мибгmentioning
confidence: 99%
“…Compared with individuals without diabetes, those with diabetes are at a 56% greater risk of death from an ST elevation myocardial infarction heart attack and at a 39% greater risk of death from a non-ST elevation MI [ 6 ]. Cardiac sympathetic hyperactivity is related to poor prognosis and fatal arrhythmias [ 7 ]. To date, noninvasive techniques such as T-wave alternans (TWA), late potentials (LP), heart rate turbulence (HRT), and heart rate variability (HRV) have been developed for this purpose.…”
Section: Introductionmentioning
confidence: 99%